A Critical Examination of the Merger of a Retail Bank and a Building Society from a Cultural Management Perspective. - Learoyd, Paul (2010)
This management project critically examines the merger of a retail bank with a building society from a cultural management perspective. The project looks at the importance of the cultural fit between the parties and reviews their approach to cultural change. The impact on the employees is assessed and informs a discussion as to the optimum process and activities required to bring about a positive outcome. It will be concluded from the literature review that culture is the very essence of an organisation.